A Livestock-Based Circular Economy Model Within the Framework of Islamic Economic Development - Aminata Sukriya; Anita Sari; St Chadijah; Fasiha (LP2M IAIN Palopo, 2026)
This article aims to formulate and thoroughly elaborate on a conceptual model of a circular economy in the livestock sector, holistically integrated with the fundamental principles of Islamic economics. Using a qualitative literature review methodology and an analytical-synthesis approach, this research examines the synergy between the core principles of the circular economy—such as reduce, reuse, recycle—and the noble values of Islamic economics, including the trusteeship of khalifah fil ardh (stewardship on Earth), the strict prohibition against wastefulness (israf), and the pursuit of Maqasid al-Shariah (the essential objectives of Islamic law). The result of this analysis is a zero-waste integrated farming model, where every output stream, including those previously considered waste, is transformed into a valuable productive input. The proposed model not only offers a technical solution for environmental sustainability and resource efficiency but also inherently integrates Islamic financial and social instruments like Musharakah, Productive Waqf, and Zakat to realize distributive justice and achieve falah (holistic well-being). Thus, this model provides a comprehensive framework for the development of the livestock sector that is not only ecologically and economically sustainable but also deeply rooted in the ethical and spiritual foundations of Islam.